Mathematical Engineering Model for Studying the Interrelated among Effective Factors in the Sugar Blood Estimation Test (Indian Journal of Forensic Medicine & Toxicology, 2021)
It is a chronic metabolic disease, which is characterized by high blood sugar, as a result of a defect in thepancreas weakens the production of insulin to the body, and spread type 2 diabetes in humans all over theworld, where there are more than a million and a half million people with diabetes. The most importantfactors contributing to the spread of this disease is eating unhealthy, excessive obesity, lack of exercise,psychological tension and genetic factor, so it is the responsibility of the state, as it must provide healtheducation to its population, and urge them to eat healthy food and reduce excess weight, and encourage themon the practice of r Intifada activity, urging them to westernize the marriage, if any diabetes in the family.Therefore, the independents and dependent variables are included using a statistical program to be analyzedand to find the degree of correlation and impact of the variables among them and to analyze and discuss theresults.
Keywords: Effective, Factors, Mathematical Engineering Model, Sugar Blood